Third parties compliance medidas de asepsia para prevenir delitos en la gestión de la cadena de suministro - Mendoza Vaez, Paul (2024)
This study analyses the inter-company relationships generated in the supply chain and underlines that the purpose of a company must transcend the merely economic to ensure its sustainability, corporate social responsibility and the satisfaction of both its stakeholders and shareholders. In addition, it details the crime prevention measures that a company must implement to avoid being affected by a defective organisation derived from its business partners. In this sense, the due diligence procedure constitutes a key process. Keywords: compliance, corporate social responsibility, third parties, due diligence.